Innovation and inter-firm technological networking: evidence from China´s information communication technology industry - Sun, Yifei; Zhou, Yu (ERDKUNDE, 2011)
This study examines the relationships between inter-firm networking and innovation within industrial clusters in a developing context. Based on a unique dataset that was collected through a large-scale survey with firms in China’s information communication technology (ICT) industry, this study systematically scrutinizes the benefits of linkages with foreign and domestic firms for innovativeness of Chinese firms. Our analyses have revealed a number of interesting patterns. First of all, Chinese firms have benefited from collaborating with both domestic and foreign firms, but particularly helpful was to maintain simultaneous technological relationships with both. Secondly, the positive impact of collaborating with domestic firms only held up to a point, above which the impact turned negative. Yet, such nonlinearity did not apply to networking with foreign firms. Thirdly, private-owned enterprises (POEs) were neither more innovative, nor more adaptive in using inter-firm technological networks than state-owned enterprises (SOEs) in China. Finally, firms in industrial satellite Suzhou and Dongguan were less innovative than those in other three major metropolitans of China – Beijing, Shanghai and Shenzhen.